Проведение репатриации польских военнопленных в Минусинском уезде Енисейской губернии в 1921 г = Provedeniye repatriatsii pol'skikh voyennoplennykh v Minusinskom uyezde Yeniseyskoy gubernii v 1921 g - ОПЛАКАНСКАЯ, Рената (Historia i Świat, 2015)
After the conclusion of the of Riga peace treaty between Poland and Soviet Russia the repatriation procedure was started. At that time in the Minusinsk's County was 418 prisoners of war. There were prisoners of the Austro-Hungarian and German armies and the former lieges of the Russian Empire. Natives of the Russian Empire accounted for one third group of Polish prisoners of war, but among them were many representatives of the nobility, as well as persons who have received education before the war. The Prisoners of war were part of labour brigades in the Yeniseijsk`s province which were sent to the logging and working industrial enterprises. All of the prisoners of war were to be registered. Special Commission including the Soviet leaders of Polish origin, dedicated to setting of Polish nationality to persons who had no documents. During the registration, some of the prisoners of war were persecuted by the Cheka. The arrested prisoners were charged with voluntary service for Kolchak, counterrevolutionary propaganda. It was a violation of the Agreement of the repatriation between Poland and Soviet Russia. After the repatriation a small group of Polish prisoners of war remained to Minusinsk`s County.